2009
DOI: 10.1002/pro.122
|View full text |Cite
|
Sign up to set email alerts
|

The thermo‐ and acido‐stable ORF‐99 from the archaeal virus AFV1

Abstract: Acidianus Filamentous Virus 1 (AFV1), isolated from acidic hot springs, is an enveloped lipid-containing archaeal filamentous virus with a linear double-stranded DNA genome. It infects Acidianus, which is a hyperthermostable archaea growing at 85°C and acidic pHs, below pH 3. AFV1-99, a protein of 99 amino acids of unknown function, has homologues in the archaeal virus families Lipothrixviridae and Rudiviridae. We determined the crystal structure of AFV1-99 at 2.05 Å resolution. AFV1-99 has a new fold, is hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Most of the early expressed genes located on the genome termini have unknown functions. SIRV2_ORF103a and SIRV2_ORF119b have a homolog in Acidianus filamentous virus 1 (AFV1), AFV1_ORF99, of which the crystal structure was determined (43). AFV1_ORF99 displays a completely novel fold from which no function prediction could be derived (43).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the early expressed genes located on the genome termini have unknown functions. SIRV2_ORF103a and SIRV2_ORF119b have a homolog in Acidianus filamentous virus 1 (AFV1), AFV1_ORF99, of which the crystal structure was determined (43). AFV1_ORF99 displays a completely novel fold from which no function prediction could be derived (43).…”
Section: Discussionmentioning
confidence: 99%
“…To date, four protein structures from lipothrixviruses (23)(24)(25)(26) have been determined. To complete structural information about Lipothrixviridae, and in particular to determine the structure of their MCPs, we have studied the Gamma-lipothrixvirus Acidianus filamentous virus 1 (AFV1).…”
mentioning
confidence: 99%
“…A tobacco etch virus (TEV) protease cleavage site was inserted between attB1 and the gene of interest. The resulting vector was transformed in Escherichia coli strain Rosetta(DE3)pLysS (Novagen) (18,19). After overnight induction with 1 mM isopropyl 1-thio-␤-D-galactopyranoside at 25°C, the cells were harvested by centrifugation for 10 min at 4,000 ϫ g. The bacterial pellets were resuspended in lysis buffer (50 mM Tris, pH 8, 300 mM NaCl, 10 mM imidazole) supplemented with 0.25 mg/ml lysozyme, 1 g/ml DNase, 20 mM MgSO 4 , and antiproteases (Complete EDTA-free antiproteases; Roche) and were frozen at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, to get insight into the biology of the Lipothrixviridae, we performed crystallographic studies of the AFV1 proteome. Although the solved structures of AFV1-102 (23) and the homologs AFV1-99 (19) and SIFV-014 (18) have not revealed any structural homologs, they have suggested that the proteins are involved in protein-protein interaction and are minor structural components, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation